1988
DOI: 10.1119/1.15697
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetry, shape invariance, and exactly solvable potentials

Abstract: It is well known that the harmonic oscillator potential can be solved by using raising and lowering operators. This operator method can be generalized with the help of supersymmetry and the concept of ‘‘shape-invariant’’ potentials. This generalization allows one to calculate the energy eigenvalues and eigenfunctions of essentially all known exactly solvable potentials in a simple and elegant manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
366
0
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(374 citation statements)
references
References 0 publications
2
366
0
6
Order By: Relevance
“…The connection between solvable potentials and supersymmetric quantum mechanics (SUSY QM) is an established fact [1,2]. Gendenshtein showed that whenever the special symmetry known as 'shape-invariance symmetry' is satisfied by the supersymmteric partner potentials V 1 and V 2 , the entire energy spectrum including eigenfunctions of the Hamiltonian can be calculated by purely algebraic means [3].…”
Section: Introductionmentioning
confidence: 99%
“…The connection between solvable potentials and supersymmetric quantum mechanics (SUSY QM) is an established fact [1,2]. Gendenshtein showed that whenever the special symmetry known as 'shape-invariance symmetry' is satisfied by the supersymmteric partner potentials V 1 and V 2 , the entire energy spectrum including eigenfunctions of the Hamiltonian can be calculated by purely algebraic means [3].…”
Section: Introductionmentioning
confidence: 99%
“…These special cases generate all known conventional additive shape-invariant superpotentials [3,11], as shown in Table I. Now that we have considered these special cases, we can systematically obtain all possible solutions.…”
mentioning
confidence: 99%
“…If the parameters differ only by an additive constant a iþ1 ¼ a i þ @, the potentials are called ''additive'' or ''translational'' shapeinvariant. All exactly solvable potentials discovered thus far that are expressible in terms of known functions are additive shape-invariant [3,11]. Several groups found these potentials by imposing various Ansätz [10,[12][13][14].…”
mentioning
confidence: 99%
“…They consist of a long range part which describes empirically the observed repulsion with a few parameters. (Dutt, et al, 1988). There are several reviews on the meson exchange approach to the NN interaction.…”
Section: Introductionmentioning
confidence: 99%